Antiviral Effect of Selenomethionine on Porcine Deltacoronavirus in Pig Kidney Epithelial Cells - Ren, Zhihua; Jia, Guilin; He, Hongyi; Ding, Ting; Yu, Yueru; Zuo, ZhiCai; Hu, Yanchun; Zhong, Zhijun; Yu, Shumin; Deng, Huidan; Shen, Liuhong; Cao, Suizhong; et al. (Frontiers in Microbiology, 2022)
Porcine deltacoronavirus (PDCoV) is an emerging porcine intestinal coronavirus in recent years, which mainly causes different degrees of vomiting and diarrhea in piglets and has caused great harm to the swine husbandry worldwide since its report. Selenium is an essential trace element for organisms and has been demonstrated to have antiviral effects. In this study, pig kidney epithelial (LLC-PK) cells were used to study the antiviral activity of selenomethionine (Se-Met )(2, 4, 8, and 16 μM) against PDCoV by detecting the replication of the virus, the expression of the mitochondrial antiviral signal protein (MAVS) protein, and the phosphorylation of interferon regulatory factor-3 (IRF-3), IFN-α, and IFN-β, and the changes in glutathione content, glutathione peroxidase, superoxide dismutase activity, and hdrogen proxide content in the cells. The results showed that Se-Met at higher than physiological concentrations (16 μM) could significantly inhibit the replication of PDCoV in LLC-PK cells and enhance the expression of MAVS protein and the phosphorylation of IRF-3. In addition, Se-Met also improved the intracellular production of IFNα/β and antioxidant capacity with increasing doses. These data suggest that the availability of selenium through selenomethionine supports the antiviral response in porcine kidney cells, and the specific mechanism is attributed to the improved cellular antioxidant capacity and activation of the MAVS pathway by Se-Met.